Inequality of Outcomes and Inequality of Opportunity in Tanzania - Zeufack, Albert G. (World Bank, Washington, DC, 2015)
The paper investigates the structure and dynamics of consumption inequality and inequality of opportunity in Tanzania. The analysis covers the period 2001 to 2012. It reveals moderate and declining levels of consumption inequality at the national level, but increasing inequalities between geographic regions. Spatial inequalities are mainly driven by the disparities of households’ characteristics and endowments across geographic locations. An important part of these endowments results from intergenerational transmission of parental background. Father’s education appears as the most important background variable affecting consumption and income in Tanzania. Without appropriate policy actions, there are few chances for the next generations to spring out of the poverty and inequality lived by their parents, engendering risks of poverty and inequality traps in the country.